2015
DOI: 10.1159/000371704
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers for Alzheimer's Disease in Patients with Frontotemporal Lobar Degeneration and Amyotrophic Lateral Sclerosis with the <b><i>C9ORF72 </i></b>Repeat Expansion

Abstract: Background: The C9ORF72 expansion is one of the most common causes of frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). The C9ORF72 expansion is associated with TDP-43 and p62 neuropathology, and amyloid plaques and neurofibrillary tangles are not common in patients with the C9ORF72 expansion. Therefore, we hypothesized that cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease [AD; Aβ1-42, total tau (T-tau) and phospho-tau] are normal in these patients. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…; Kämäläinen et al . ). Some studies showed specific changes in C9orf72 mutation carriers with ALS including increased CSF concentrations of poly(GP) expression as a result of the hexanucleotide repeat extension (Su et al .…”
Section: Genetic Ftld Casesmentioning
confidence: 97%
“…; Kämäläinen et al . ). Some studies showed specific changes in C9orf72 mutation carriers with ALS including increased CSF concentrations of poly(GP) expression as a result of the hexanucleotide repeat extension (Su et al .…”
Section: Genetic Ftld Casesmentioning
confidence: 97%
“…The patients with such altered biomarker status fulfilled the clinical criteria of the behavioral variant FTD with no clinical signs of AD. In this study, neuropathological confirmation was available only for one patient, showing TAR DNA-binding protein 43 (TDP-43) pathology, but no A or tau pathology [19]. Albeit the reason for the decrease in the CSF 1-42 levels remains thus far unknown, these results suggest that decreased CSF A 1-42 5 levels may not exclude C9orf72 repeat expansion-carrying FTD patients in clinical diagnostics [19].…”
Section: Introductionmentioning
confidence: 78%
“…Increased levels of total and phosphorylated tau and decreased levels of A 42 peptides in the cerebrospinal fluid (CSF) are used as diagnostic biomarkers for AD [17,18]. We have previously reported that 25% of Finnish C9orf72 repeat expansion-carrying FTD patients show decreased CSF A 1-42 levels [19]. The patients with such altered biomarker status fulfilled the clinical criteria of the behavioral variant FTD with no clinical signs of AD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that AD-associated neuropathology is occasionally linked to the C9ORF72 -associated FTLD [27]. In addition, similarly to the AD patients, abnormally low CSF Aβ 1–42 levels have been identified in over 20% of the FTLD patients with the C9ORF72 expansion [28]. As AD and vascular dementia are the most frequent cognitive disorders showing comorbidity with iNPH, the pathological features perceived in iNPH most commonly represent both vascular and AD-related changes [29].…”
Section: Discussionmentioning
confidence: 99%